Surface species investigation of Ni-Fe catalysts of CO₂ hydrogenation by TD MS analysis - Meshkini Far, R.; Dyachenko, A.; Bieda, O.; Ischenko, O. (Поверхность, 2017)
The condition of Ni-Fe catalysts’ surface was investigated by the method of thermally programmed desorption with mass spectral analysis of desorbed particles (TD MS). TD spectra indicated the desorption of CO₂ (m/z = 44), CO (m/z = 28) and H₂O (m/z = 18) particles from the surface of samples with high and low catalytic activity in the reaction of CO₂ hydrogenation. Intermediate compounds CHO*, CH₂O* were not observed in the TD profiles for all investigated catalysts. On the basis of catalytic performance results and thermal desorption data it can be suggested that process of CO₂ hydrogenation over Ni-Fe catalysts proceeds via direct hydrogenation of CO₂ to CH₄.